Analytical analysis of Roman amphorae - Adilbekov, Dauren (2017)
Abstract: The analysis of organic residues present in ancient pottery can give important information for archaeologists. Diets, habits, technologies and original use of the vessels can be identified through this studies. Fourier transform infrared spectroscopy (FT–IR) and gas chromatography coupled with mass spectrometry (GC–MS) were used in order to analyse organic resinous materials from the interior surfaces of Roman amphorae belonging to the archaeological collection of DRASSM and Museum of Arles Antique. In addition, wine amphorae from Grand Congloué 2 shipwreck were analysed. The FTIR spectra obtained by the technique of KBr micropellets, prepared directly with the materials scraped from the amphora without any further sample preparation, provided enough information to establish their diterpenoic nature. GC–MS enabled to identify dehydroabietic acid, 7-oxodehydroabietic acid, 7-hydroxy-dehydroabietic acid, 15-hydroxy-7-oxodehydroabietic acid, methyl dehydroabietate, retene. The presence of diterpenoids and retene provided evidence that the amphorae examined were waterproofed with a pitch produced from resinous wood of plants from the Pinaceae family or mainly consist of Coniferae species. Moreover presence of retene in samples indicates that pitch was heated. Wine and fish amphorae were studied. Some fish amphorae samples did not show the presence of pitch in GC-MS analyses. This work studies for the first time pitch of an fish amphorae in the laboratory of IMBE.